Pelaksanaan Olahraga Bulu Tangkis Siswa Tunagrahita - Nur Fahmi; Jon Efendi (PAKAR Pendidikan, 2019)
This study aims to describe the implementation of badminton for intelectuall disability students in SLBN 1 Bukittinggi which includes implementation, obstacles, and solutions. The subjects in this study were sports counseling teachers. Supporting information was obtained from school principals, student representatives, and students participating in badminton sports activities. Data collection techniques used are observation, interviews, and documentation. The results showed that the implementation of tagging feathers was carried out with warm-up preparation before the exercise in the form of running around the field, training activities carried out three times a week, namely on Monday, Wednesday, and Friday starting from 13.00 - 16.00. The exercise is carried out using demonstration methods and training methods. Obstacles encountered in the implementation of badminton sport are students more often following moods, lack of motivation, for the beginner giving material requires considerable time and the solutions taken are giving direction and support to students and fostering students since elementary school as the next generation.